A world without privacy : What Law Can and Should Do? - Sarat, Austin (Libros electrónicos en Ebscohost, 2006)
Recent revelations about America's National Security Agency offer a reminder of the challenges posed by the rise of the digital age for American law. These challenges refigure the meaning of autonomy and of the word'social'in an age of new modalities of surveillance and social interaction. Each of these developments seems to portend a world without privacy, or in which the meaning of privacy is transformed, both as a legal idea and a lived reality. Each requires us to rethink the role of law, can it keep up with emerging threats to privacy and provide effective protection against new forms of surveillance? This book offers some answers. It considers different understandings of privacy and provides examples of legal responses to the threats to privacy associated with new modalities of surveillance, the rise of digital technology, the excesses of the Bush and Obama administrations, and the continuing war on terror.